Transversal Practices between Bourgeois Cosmopolitanism and Fervent German Nationalism. The Schillerverein in Trieste as an Example of the In-between in the Alps-Adriatic Region - Holfelder, Ute; Katschnig, Gerhard; Schemmer, Janine; Schönberger, Klaus (Traditiones, 2017)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">In the course of the Europe-wide Schiller celebrations commemorating the centenary of Friedrich Schiller’s birth, a Schillerverein (Schiller Society) was founded in Trieste 1859. It was made up of members of different ethnicities and religious confessions. One of the main aims of the society was to contribute to the cultural life of Trieste by means of (popular) scholarly lectures, concerts, theater performances, dances, and excursions. <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"><span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Ob stoletnici rojstva pesnika Friedricha Schillerja, ki so ga proslavljali povsod po Evropi, so v Trstu leta 1859 ustanovili društvo Schillerverein. Njegovi člani so bili različnih narodnosti in religioznih prepričanj. Eden glavnih ciljev društva je bil z različnimi poljudnimi predavanji, gledališkimi predstavami, plesi in ekskurzijami obogatiti kulturno življenje v Trstu.